UPAYA MENURUNKAN JAJANAN TIDAK SEHAT PADA ANAK USIA DINI KELOMPOK B3 MELALUI KOLABORASI ORANG TUA DAN GURU DI RA DARUSSALAM - Elianti Wijaya; Abdul Muiz Rouf; Muhammad Azka Maulana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The consumption of unhealthy snacks among young children is a serious issue that can disrupt health, growth, and learning concentration. This study aims to describe efforts to reduce the consumption of unhealthy snacks through collaboration between parents and teachers at RA Darussalam. This research used an action research method with a qualitative approach. Data were collected through participatory observation, in-depth interviews with teachers and parents, and documentation studies. The research subjects were 18 children from group B3, their parents, and teachers at RA Darussalam. The results showed that collaboration between parents and teachers was formed through regular communication, joint educational activities (such as